2013
DOI: 10.1039/c3lc41417e
|View full text |Cite
|
Sign up to set email alerts
|

Lung assist device: development of microfluidic oxygenators for preterm infants with respiratory failure

Abstract: This paper reports the development of microfluidic oxygenator (MFO) units designed for a lung assist device (LAD) for newborn infants. This device will be connected to the umbilical vessels like the natural placenta and provide gas exchange. The extracorporeal blood flow is only driven by the pressure difference between the umbilical artery and vein without the use of external pumps. The LAD is designed for use in ambient air (~21% of 760 mmHg). The main focus of this paper is the presentation of the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 26 publications
2
96
0
Order By: Relevance
“…Challenges associated with scaling of microfluidic oxygenator devices have been addressed in a recent review 23 , and have been debated in subsequent communications. 24–25 Most reports of microfluidic oxygenators have been limited to blood flow rates of 5 mL/min or less; 17, 18, 21, 2629 one has reported blood flow rates as high as 40 mL/min, but the oxygen content of the blood appeared to drop below commercial oxygenator oxygen transfer levels (5 volume percent oxygen relative to the total blood volume) above 10 mL/min blood flow rates. 30 Another recent report from Rieper et al has demonstrated blood oxygen transfer at blood flow rates as high as 60 mL/min, clearly a major advance over most of the microfluidic literature [T. Rieper, C. Muller and H. Reinecke, However, this report does not describe an approach to ensure that blood flow patterns in the channel structures are designed in a manner to avoid sharp corners and non-physiologic and potentially deleterious flow paths.…”
Section: Resultsmentioning
confidence: 99%
“…Challenges associated with scaling of microfluidic oxygenator devices have been addressed in a recent review 23 , and have been debated in subsequent communications. 24–25 Most reports of microfluidic oxygenators have been limited to blood flow rates of 5 mL/min or less; 17, 18, 21, 2629 one has reported blood flow rates as high as 40 mL/min, but the oxygen content of the blood appeared to drop below commercial oxygenator oxygen transfer levels (5 volume percent oxygen relative to the total blood volume) above 10 mL/min blood flow rates. 30 Another recent report from Rieper et al has demonstrated blood oxygen transfer at blood flow rates as high as 60 mL/min, clearly a major advance over most of the microfluidic literature [T. Rieper, C. Muller and H. Reinecke, However, this report does not describe an approach to ensure that blood flow patterns in the channel structures are designed in a manner to avoid sharp corners and non-physiologic and potentially deleterious flow paths.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental setup for testing the LAD was similar to the one that we had previously used for SOUs and is described in our previous article (6).…”
Section: Characterizing Gas Exchange and Pressure Drop In Vitro: Expementioning
confidence: 99%
“…Microfluidic devices are ideal for applications that require low priming volume and are being investigated for use as oxygenators, although they have not been tested in humans or animals. In a recent article we published model calculations for the concept and described the development of such a device (6). We demonstrated that in comparison with alternate methods for neonatal extracorporeal membrane oxygenation based on the use of hollow-fiber oxygenators, the microfluidic approach is superior, as it provides a high surface-to-volume ratio with a low filling volume and high gas exchange.…”
Section: Introductionmentioning
confidence: 99%
“…3,19,47,64,67 Notably, development of microfluidic oxygenator units to promote gas exchange has been of significant interest in the field. 17,31,42,57,62 Microfluidic networks may have utility in extracorporeal devices to trap bubbles and emboli as well as measure levels of reagents and toxins. 25,26,29,36 However, the role of the microfluidic network geometry in the thrombogenicity of devices such as extracorporeal oxygenation machine (ECMO), left ventricular assist devices, and nanomembrane hemodialysis cassettes is not well defined.…”
Section: Discussionmentioning
confidence: 99%